Bioinspired Injectable Self-Healing Hydrogel Sealant with Fault-Tolerant and Repeated Thermo-Responsive Adhesion for Sutureless Post-Wound-Closure and Wound Healing - Liang, Yuqing; Xu, Huiru; Li, Zhenlong; Zhangji, Aodi; Guo, Baolin (Nano-Micro Letters, 2022)
Hydrogels with multifunctionalities, including sufficient bonding strength, injectability and self-healing capacity, responsive-adhesive ability, fault-tolerant and repeated tissue adhesion, are urgently demanded for invasive wound closure and wound healing. Motivated by the adhesive mechanism of mussel and brown algae, bioinspired dynamic bonds cross-linked multifunctional hydrogel adhesive is designed based on sodium alginate (SA), gelatin (GT) and protocatechualdehyde, with ferric ions added, for sutureless post-wound-closure. The dynamic hydrogel cross-linked through Schiff base bond, catechol-Fe coordinate bond and the strong interaction between GT with temperature-dependent phase transition and SA, endows the resulting hydrogel with sufficient mechanical and adhesive strength for efficient wound closure, injectability and self-healing capacity, and repeated closure of reopened wounds. Moreover, the temperature-dependent adhesive properties endowed mispositioning hydrogel to be removed/repositioned, which is conducive for the fault-tolerant adhesion of the hydrogel adhesives during surgery. Besides, the hydrogels present good biocompatibility, near-infrared-assisted photothermal antibacterial activity, antioxidation and repeated thermo-responsive reversible adhesion and good hemostatic effect. The in vivo incision closure evaluation demonstrated their capability to promote the post-wound-closure and wound healing of the incisions, indicating that the developed reversible adhesive hydrogel dressing could serve as versatile tissue sealant. Highlights: 1 Mussel and brown algae inspired dual-bionic bioadhesive cross-linked by dynamic bonds exhibits good self-healing capacity and sufficient adhesive strength. And the adhesive hydrogel shows temperature-dependent reversible adhesive behavior, and could achieve fault-tolerate adhesive application and repeated tissue adhesion. 2 The coordination interaction between ferric ions and protocatechualdehyde equips the hydrogel with photothermal antibacterial effect. 3 The injectable adhesive with antioxidation and good hemostatic effect shows promising application in tissue sealant and wound closure.